Auricular therapy improves gastrointestinal function in patients with gynecological laparoscopic surgery: A protocol for systematic review and meta analysis. Issue 49 (4th December 2020) - Hu, Ying; Cheng, Xianying; Su, Xinglin; Fu, Yun
Abstract: Background: Gynecological laparoscopic surgery is the main method to treat gynecological diseases, but postoperative gastrointestinal reactions are more common in patients. Auricular therapy, as a characteristic therapy of Traditional Chinese Medicine, can improve gastrointestinal symptoms such as nausea and vomiting by stimulating the conduction of acupoints through the nervous system on internal organs, but there are studies questioning the efficacy of auricular therapy. Therefore, the purpose of this study is to prove the efficacy and safety of auricular therapy in promoting gastrointestinal function recovery after gynecological laparoscopic surgery, and to provide reference value for future clinical practice. Methods: To search English databases (PubMed, Excerpta Medical Database [Embase], Web of Science, the Cochrane Library) and Chinese databases (Chinese National Knowledge Internet [CNKI], WanFang, Viper, Chinese Biomedical Literature Database) by computer, and conduct a randomized controlled trial on the effect of aural point therapy on gastrointestinal function recovery of patients after gynecological laparoscopic surgery from the establishment of the database to October 2020. Two researchers independently evaluate the quality of the included studies and extract the data, and meta-analysis of the included literature is carried out using RevMan5.3 software. Results: In this study, the efficacy and safety of auricular therapy in the recovery of gastrointestinal function after gynecological laparoscopic surgery are evaluated from the aspects of first anal exhaust time, bowel sound recovery time, and incidence of gastrointestinal complications. Conclusion: This study will provide reliable evidence-based evidence for auricular therapy in the treatment of gastrointestinal function after gynecologic laparoscopic surgery. Ethics and dissemination: Private information from individuals will not be published. This systematic review also does not involve endangering participant rights. Ethical approval was not required. The results may be published in a peer-reviewed journal or disseminated at relevant conferences. OSF Registration number: DOI 10.17605 / OSF.IO / ZSPGA